Effect of environmental concern and skepticism in the consumption green products in brazilian retail - Braga Junior, Sergio Silva [UNESP]; Merlo, Edgard Monforte; Freire, Otavio B. Lamonica; Da Silva, Dirceu; Quevedo-Silva, Filipe (My University, 2016)
Current paper analyzes the interference of skepticism and environmental concern in people's awareness with regard to purchase intention and purchase declaration for green products on the grocery retail. A survey with 905 people was conducted in which the moderating effect of skepticism between purchase intention and purchase declaration could be perceived. Results demonstrate that consumers give more importance to their buying routine and past experience. It may be stated that the consumption of green products on the retail should bring about a focus on changes of habits and on the breaking of paradigms by the market (consumer and retail) since skepticism is a powerful moderator between purchase intention and purchase declaration of green products.
Keywords: Environmental concern; Green products; Grocery; Purchase intention; Skepticism